Produção de hidrogênio a partir da água residuária e do bagaço da extração de fécula de mandioca em AnSBBR. - Tonello, Tamiris Uana (2022)
Industries that produce cassava starch or flour generate a considerable amount of solid and liquid waste in their production process. These residues exhibit high concentrations of organic matter that favor the production of bioenergy, such as methane and hydrogen. The anaerobic digestion system with two residues (solid and liquid) in reactors represents a relevant alternative for the production of bioenergy. Therefore, this research aimed to evaluate the production of hydrogen from wastewater (ARF) and bagasse (BM) derived out of the cassava starch extraction process in an anaerobic reactor operated in sequential batch with immobilized biomass (AnSBBR). The study consisted of three main phases: I) Batch Tests (BA) – preliminary tests; II) hydrogen production in AnSBBR; III) hydrogen production in AnSBBR with inoculum from native microbiota of cassava bagasse. Phase I included the following tests: i) batch tests (BA) carried out to evaluate the effect of thermal and chemical treatment of the inoculum on the production of hydrogen; ii) batch tests to evaluate hydrogen production using cassava bagasse as substrate. In Phase II of the study, hydrogen production in AnSBBR was evaluated by varying the volumetric organic load (COV, from 2.4 to 9.3 gCT L-1 , and based on total volatile solids, COV from 0.8 gSVT L-1d -1 ), the cycle time (TC, 6 to 24h), and the form of the bagasse (in natura, dry and broken down and dry and crushed) as well as the method of introducing the cassava bagasse into the reactor (together with the feed pump or directly on the support medium). In these tests, wastewater from the cassava starch industry and synthetic wastewater were used as liquid substrate. In Phase III, hydrogen production with bagasse in the AnSBBR reactor (Concentration of 2.5 gCT L-1 and 24- hour TC) was evaluated using the inoculum obtained from the native microbiota of cassava bagasse (bagasse fermenting for 80 days). In Phase I, it was verified that the test that presented the highest accumulated volumetric productivity (AVP) (84.71 mL H2) was obtained with the inoculum thermally treated, with nutrient solution and cassava bagasse as carbon source. Throughout Phase II, in the tests on AnSBBR, the one with dry and broken down BM, added only once along with the support medium, fed with ARS with sucrose, showed higher volumetric productivity (1,18 LH2 L -1 d -1 ). In Phase III, the batches with inoculum from the BM native microbiota with nutrient solution showed the highest accumulated volumetric production (24 mLH2) and in AnSBBR the test with inoculum of the BM native microbiota together with BM in natura and fed with ARF reached maximum hydrogen volumetric productivity in the first days (0.178 LH2 L -1 d -1 ) and yield (0.09 molH2 kgCarb-1 ). It can be concluded that the highest hydrogen production was with the lowest amount of bagasse added and with ARS as a power supply.